2016
DOI: 10.1097/sla.0000000000001552
|View full text |Cite
|
Sign up to set email alerts
|

Bile Acids Increase Independently From Hypocaloric Restriction After Bariatric Surgery

Abstract: The levels of serum BA increase after bariatric surgery independently from caloric restriction, whereas the level of WAT TGR5 protein is unaffected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
50
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(55 citation statements)
references
References 26 publications
5
50
0
Order By: Relevance
“…These reports thus indicate that serum bile acid levels were increased by bariatric surgery through normalizing of the gut microbiota profile and possibly associated with improved glucose and lipid metabolism, including insulin resistance after metabolic surgery. In addition, vertical sleeve gastrectomy, but not a hypocaloric diet, increased circulating serum bile acid level in obese patients with diabetes [38]. These findings may support the notion that LSG increased preheparin LPL level independent of the decrease in BMI.…”
Section: Discussionsupporting
confidence: 77%
“…These reports thus indicate that serum bile acid levels were increased by bariatric surgery through normalizing of the gut microbiota profile and possibly associated with improved glucose and lipid metabolism, including insulin resistance after metabolic surgery. In addition, vertical sleeve gastrectomy, but not a hypocaloric diet, increased circulating serum bile acid level in obese patients with diabetes [38]. These findings may support the notion that LSG increased preheparin LPL level independent of the decrease in BMI.…”
Section: Discussionsupporting
confidence: 77%
“…In large part, human studies have confirmed that fasting or postprandial total bile acid concentrations are increased following RYGB (Ahmad et al, 2013; Albaugh et al, 2015; De Giorgi et al, 2015; Ferrannini et al, 2015; Gerhard et al, 2013; Jahansouz et al, 2016; Jørgensen et al, 2015; Nakatani et al, 2009; Pournaras et al, 2012; Simonen et al, 2012; Steinert et al, 2013; Werling et al, 2013b) and BPD (Ferrannini et al, 2015; Nakatani et al, 2009). The effects of VSG on bile acid levels is mixed with some showing increased plasma concentrations (Jahansouz et al, 2016; Khan et al, 2016; Steinert et al, 2013), but others detecting no change (Belgaumkar et al, 2016; Escalona et al, 2016; Nakatani et al, 2009). As expected, studies examining adjustable gastric banding, known to be an exclusively restrictive procedure, show no changes in circulating bile acids (Kohli et al, 2013a; Pournaras et al, 2012).…”
Section: Bile Acids and Obesitymentioning
confidence: 98%
“…While caloric restriction does not appear to affect bile acid pool size or composition in man (Duane et al, 1976; Jahansouz et al, 2016; van Nierop et al, 2016), the few studies that have examined the effect of altering dietary fat source and fat composition, commonly occurring in the postoperative period, have yielded inconsistent effects (Andersén and Hellström, 1980; Lindstedt et al, 1965). Diet is known to induce changes in bile acid species and total bile acid pool (Bisschop et al, 2004; M.…”
Section: Bile Acids and Obesitymentioning
confidence: 99%
“…On the other hand, bile acid concentrations have been found to be increased in obese patients with type 2 diabetes [31] . Bariatric surgery was found to increase bile acids, but a hypocaloric diet, which induced similar weight loss, was associated with a reduction in the level of uncongugated bile acids [32] , suggesting that bile acid changes are not the main reason for improvement in glucose tolerance following gastric bypass operations. FXR activation of L cells in the ileum by the bile acids may be one mechanism involved in the improvement of diabetes [33] .…”
Section: Effect Of Bile Acids On Lipid and Glucose Metabolismmentioning
confidence: 99%